Silver sequestration of halides for the activation of Pd(OAc) 2 catalyzed Mizoroki-Heck reaction of 1,1 and 1,2 - Disubstituted alkenes: Ag Sequestration for Pd catalyzed Heck reaction- disubstituted alkenes - Bangar, Pronnoy G.; Jawalkar, Priyanka R.; Dumbre, Swapnil; Patil, Dharmaraj; Iyer, Suresh (Applied Organometallic Chemistry, 2017)
A ligand free catalytic system consisting of Pd(OAc)2 (cat) and stoichiometric quantities of silver salts, AgOAc or AgBF4, exhibit high efficiency in the Mizoroki-Heck arylation, transforming aryl iodides and 1,1 as well as 1,2 disubstituted alkenes into 1,1,2 – trisubstituted aryl alkenes in excellent yields in very short reaction times.
Keywords: 1; 1-disubstituted alkenes; 2-disubstituted alkenes; AgBF4; AgOAc; Mizoroki-Heck reaction

Mizoroki-Heck reaction of 1,2-disubstituted aryl alkenes: variables of synthesis, solvent and ligand modulation of reactivity - Bangar, Pronnoy G.; Jawalkar, Priyanka R.; Dumbre, Swapnil R.; Raut, Pallavi K.; Patil, Dharmaraj J.; Tv, Neethu; Sudhakaran, Shana; Iyer, Suresh (Synthetic Communications, 2020)
Reaction of aryl iodides with 1,2-disubstituted aryl alkenes in the presence of TBABr/TBACl gave high yields of the Mizoroki-Heck product. Phosphine ligands were used for the modulation of reactivity and stereoselectivity, for the reaction of 4-iodoanisole with cinnamaldehyde. tert-Bu3P.HBF(4)gave the highest E:Z ratio of 1:0.08. The use of PEG-200 and PEG-400 as solvent could activate the reaction of aryl iodides with various 1,2-disubstituetd aryl alkenes.
Keywords: 12-Disubstituted aryl alkenes; 400; ligand effect; Mizoroki-Heck reaction; PEG 200; TBABr

Bimetallic nano alloy architecture on a special polymer: Ni or Cu merged with Pd for the promotion of the Mizoroki-Heck reaction and the Suzuki-Miyaura coupling - Patil, Vijay P.; Kashid, Abhijit A.; Solanki, Bhanupratap S.; Kharul, Ulhas K.; Iyer, Suresh (Journal of Chemical Sciences, 2021)
Novel Ni-Pd and Cu-Pd bimetallic nano alloys was designed and heterogenized on the highly robust ABPBI [poly(2,5-benzimidazole)] polymer in high yields using NaBH4 as reducing agent. These were versatile ligand free catalysts for the Mizoroki-Heck reaction and Suzuki-Miyaura coupling. The bimetallic Ni-Pd-ABPBI catalyst for the Mizoroki-Heck reaction of 4-iodo anisole could be recycled 5 times with high yields. Aryl bromides could also be activated for the Mizoroki-Heck reaction using Cu-Pd-ABPBI NP catalysts, with moderate yields. Graphic abstractSynopsis Novel bimetallic Ni-Pd and Cu-Pd nano alloys, heterogenized on the robust ABPBI [poly(2,5-benzimidazole)] polymer using NaBH4 as reducing agent, is described. These were versatile ligand free, noble metal conservative catalysts, for the Mizoroki-Heck reaction and the Suzuki-Miyaura coupling. Aryl bromides were activated for the Mizoroki-Heck reaction using the Cu-Pd-ABPBI catalyst.
Keywords: Bimetallic nano alloys; Cu-Pd-ABPBI; Mizoroki-Heck reaction; Ni-Pd-ABPBI; Suzuki coupling

Bimetallic Ni-Pd synergism-mixed metal catalysis of the mizoroki-heck reaction and the suzuki-miyaura coupling of aryl bromides - Kashid, Abhijit A.; Patil, Dharmaraj J.; Mali, Ramling D.; Patil, Vijay P.; Neethu, T. V.; Meroliya, Heena K.; Waghmode, Shobha A.; Iyer, Suresh (Catalysis Letters, 2021)
A combination of Pd and Ni complexes activated aryl bromides for the thermal Mizoroki-Heck reaction and Suzuki coupling giving high yields in short reaction times. A thermal redox mechanism probably occurs whereby Ni complex transfers electron and reduces the Pd (II) to Pd (0) which then takes the reactants through the standard protocol of oxidative-addition, migratory insertion and reductive elimination, typical for the Mizoroki-Heck reaction and the Suzuki coupling. [GRAPHICS] .
Keywords: Bimetallic catalysis; Mizoroki-Heck; Nickel complexes; Pd(OAc)2; Suzuki coupling

Bimetallic Ni–Pd synergism—mixed metal catalysis of the mizoroki-heck reaction and the suzuki–miyaura coupling of aryl bromides - Kashid, Abhijit A.; Patil, Dharmaraj J.; Mali, Ramling D.; Patil, Vijay P.; Neethu, T. V.; Meroliya, Heena K.; Waghmode, Shobha A.; Iyer, Suresh (Catalysis Letters, 2021)
A combination of Pd and Ni complexes activated aryl bromides for the thermal Mizoroki-Heck reaction and Suzuki coupling giving high yields in short reaction times. A thermal redox mechanism probably occurs whereby Ni complex transfers electron and reduces the Pd (II) to Pd (0) which then takes the reactants through the standard protocol of oxidative-addition, migratory insertion and reductive elimination, typical for the Mizoroki-Heck reaction and the Suzuki coupling.

Oxime ligands for Pd catalysis of the mizoroki-heck reaction, suzuki-miyaura coupling & annulation reactions - Bangar, Pronnoy G.; Nahide, Pradip D.; Meroliya, Heena K.; Waghmode, Shobha A.; Iyer, Suresh (Synthetic Communications, 2021)
Monodentate and bidentate chelating oximes are readily available ligands for the Pd catalysis of the Mizoroki-Heck reaction and the Suzuki coupling. High yields were obtained in the Suzuki coupling in aqueous dioxane with TBABr as additive. The oximes can be easily synthesized from the corresponding ketones or aldehydes and thus provide a very large number of nitrogen-based ligands. They have the advantage of not undergoing oxidative degradation, common for phosphine ligands. Chelating oximes with Pd(OAc)(2), activate aryl iodides to give high yields of the substitution products in the Mizoroki-Heck reactions as well as the Suzuki coupling. Acetophenone oxime ligand with Pd(OAc)(2), catalyzed the reaction of aryl iodides with 1,2-disubstituted alkenes in moderate to high yields. As a test example, the LaRock indole annulation and synthesis of isocoumarin were achieved with acetophenone oxime ligand and Pd(OAc)(2)in high yields.
Keywords: Isocoumarin; LaRock annulation; Mizoroki-Heck reaction; oximes; Suzuki coupling

Oxime ligands for Pd catalysis of the mizoroki–heck reaction, Suzuki–Miyaura coupling & annulation reactions - Bangar, Pronnoy G.; Nahide, Pradip D.; Meroliya, Heena K.; Waghmode, Shobha A.; Iyer, Suresh (Synthetic Communications, 2021)
AbstractMonodentate and bidentate chelating oximes are readily available ligands for the Pd catalysis of the Mizoroki–Heck reaction and the Suzuki coupling. High yields were obtained in the Suzuki coupling in aqueous dioxane with TBABr as additive. The oximes can be easily synthesized from the corresponding ketones or aldehydes and thus provide a very large number of nitrogen-based ligands. They have the advantage of not undergoing oxidative degradation, common for phosphine ligands. Chelating oximes with Pd(OAc)2, activate aryl iodides to give high yields of the substitution products in the Mizoroki–Heck reactions as well as the Suzuki coupling. Acetophenone oxime ligand with Pd(OAc)2, catalyzed the reaction of aryl iodides with 1,2-disubstituted alkenes in moderate to high yields. As a test example, the LaRock indole annulation and synthesis of isocoumarin were achieved with acetophenone oxime ligand and Pd(OAc)2 in high yields.

Bimetallic quantum dots (Cu-Pd, Ni-Pd) catalyzed reaction of bromo arenes with alkenes and aryl boronic acids - Raut, Pallavi K.; Meroliya, Heena K.; Dumbre, Swapnil R.; Patil, Vaishali N.; Solanki, Bhanupratap S.; Waghmode, Shobha A.; Iyer, Suresh (Indian Journal of Chemistry, 2023)
Bimetallic quantum dots (Cu-Pd and Ni-Pd) are active ligand-free catalysts for the alkenylation and arylation of aryl bromides. The catalysts are easy to synthesize by benign green protocols and characterized by various techniques. The bimetallic QD catalysts synthesized thus are superior to Pd(OAc)2 or other Pd NP catalysis of alkenylation reactions of aryl bromides with similar E-selectivity. The reaction of aryl bromide with aryl boronic acid is facile with high yields.
Keywords: Aryl bromides; Bimetallic QDs catalysis; Cu-Pd; Mizoroki-Heck; Ni-Pd; Suzuki coupling

Oxime ligands: organometallic synthesis and catalysis - Iyer, Suresh (SYNTHETIC COMMUNICATIONS, 2024)
Ligands are at the heart of coordination chemistry. They conjure the magic of transition metals expressed in organometallic catalysis. Phosphine or P-ligands have found vast utility in transition metal chemistry, though demanding tedious synthesis. Several N, S-based ligands also find application in organometallic chemistry. Oximes are easily derived from aldehydes and ketones by simple reactions with hydroxylamine. Thus, an extensive library of oximes is available with different structural and electronic variations essential for coordination chemistry and catalysis. Several compounds with complex structural features, unavailable for phosphorous ligands, can be readily converted into active oxime ligands in a single derivatization step. Oxime ligands and metal complexes are applied in synthesizing diverse organic molecules and thus versatile ligands in organotransition metal chemistry.
Keywords: cobaloxime; Cross-coupling; oxime palladacycles; oximes; radical cyclization